The effect of virtual audiences on music performance anxiety - Castle-Green, Teresa Anne (2015)
Music Performance Anxiety (MPA) is experienced by a large number of musicians throughout their careers. In many cases this anxiety can have debilitating consequences for the performer preventing them from delivering a performance to the standard they are capable of. Very little research has been conducted within the field of Human-Computer Interaction (HCI) into the ways in which technology can assist musicians with learning to manage their MPA. This paper builds on the limited body of research to test the potential effectiveness of a virtual audience as a tool in the treatment of MPA. Three performer interviews and a literature review of audience behaviour lay the foundation for the design of a virtual music festival that houses three different types of virtual audience. The audiences are designed to give positive, negative or neutral feedback to experienced musicians whilst they perform songs that they are confident with and songs that they are not. The aim of the study was to evaluate the extent to which a virtual audience can affect the onset of MPA and the extent to which performer confidence levels impact any effect, thus investigating its potential use for virtual reality (VR) exposure therapy to treat MPA. Results show a significant effect of audience type on self-reported state anxiety and performers’ self-rating of performance. Mean scores showed the highest anxiety scores and the lowest performance ratings in the negative audience conditions, demonstrating that approval feedback from virtual audiences can affect the onset of MPA. The use of anxiety management techniques is also identified through post-evaluation interviews with performers, adding further support to this effect. High levels of copresence were found throughout all conditions indicating that the participants were immersed and felt that they were interacting with the audience. This work supports pervious virtual audience research in the field of public speaking anxiety and also builds on the limited research of using virtual audiences for MPA. Strong potential is indicated for the use of virtual audiences in exposure treatment for MPA.